The gospel of Jesus : in search of the original "good news" - Robinson, James M. (James McConkey), 1924- (San Francisco : HarperSanFrancisco, 2005)
"Jesus's original gospel has been lost from sight, hidden behind the version preferred by the church. We have put him on a pedestal, rather than walked in his footsteps. In The Gospel of Jesus, James M. Robinson, the preeminent expert on the earliest sources of information about Jesus, provides the primary texts in all their unvarnished honesty to get to the true historical message of Jesus - what Robinson calls "a brittle, upsetting, comforting, challenging gospel." The Gospel of Jesus draws on a combination of the most ancient and authentic texts to reveal what Jesus really said and to illuminate what he may still have to say to us today." "Drawing on the earliest Gospel, Mark, plus the source for Matthew and Luke, known as "Q," as well as from Jewish sources such as the Dead Sea Scrolls and the ancient extra-biblical Gnostic texts discovered at Nag Hammadi, Robinson not only reconstructs the good news Jesus preached and practiced two thousand years ago, but shows how relevant his message still is - and how we can apply it to our lives today."--BOOK JACKET.
Introduction : the focus on Jesus' gospel -- 1. The lost gospel of Jesus -- 2. The sayings gospel Q -- 3. Jesus was a Galilean Jew -- 4. What we do and do not know about Jesus -- 5. Jesus was converted to John -- 6. Jesus' lifestyle underwritten by God himself -- 7. Jesus' trust in God -- 8. Jesus' view of himself -- 9. The end as the beginning -- 10. The gospel of Jesus and the gospel of Paul -- Epilogue : where do we go from here?
Includes bibliographical references.
Keywords: Jesus Christ -- Historicity; Q hypothesis (Synoptics criticism)